Alveolus Reconstruction Using Submental Artery Flap After Wide Excision Of Maxillary Adenoid-Cystic Carcinoma (Journal of Pharmaceutical Negative Results, 2023)
Introduction The reconstruction of intraoral soft tissue and bony defects is important to restore function and esthetics. For large defects, there is a need for regional pedicled flaps or free flaps. The hard palate separates the nasal and oral cavities. Due to the small remaining surface area between the flap and the palate after surgical resections, an optimal blood supply to the flap is required for reconstructions of the hard palate. Case Report This article demonstrates the immediate reconstruction with submental island flap of a patient with partial maxillectomy after wide excision of maxillary adenoid cystic carcinoma and discusses a brief overview of this flap. Conclusion The submental island flap is an effective and reliable method for intraoral reconstruction of large soft-tissue defects in the oral cavity. Morbidity at the donor site is low and the remaining scar is unremarkable. Head and neck surgeons familiar with the facial artery and its branching pattern make this flap an appropriate choice for clinical practice.